THE ROLE OF COORDINATION ABILITIES AT THE INITIAL STAGE OF TRAINING YOUNG ROWERS - Azimov Zikirillo (Research Focus International Scientific Journal, 2023)
The article reveals the role and importance of developing of balance skills and the feeling of water when learning the technique of canoe paddling.